Radziecka procedura cywilna: totalitarna czy nowoczesna? - Stawarska-Rippel, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
Soviet civil procedure was codified twice, in 1923 and 1964. In both cases, the codification of Soviet civil proceedings was caused by the political liberalization occurring during relevant periods. It was therefore a good time for the codification work to adapt, at least to some extent, traditional solutions; simultaneously the desire to politicize the civil procedure resulted in the emergence of new legal institutions. The imposition of far-reaching restrictions on the principle of a free exercise by the parties of their rights was the characteristic and specific element of totalitarian regimes. It is an altogether too common misconception to perceive the confinement of the adversarial principle asan extraordinary and defining component of the Socialist civil procedure because the pursuit of truth in a material sense and the introduction of inquisitorial elements in civil proceedings had already been known in European legal systems. The phenomenon of the socialization of law had changed the perspective concerning the goals of modern civil trial in Europe. In particular, the codes of the Swiss cantons of Bern and Zurich, as well as the Hungarian civil procedure, had significantly widened the scope of the inquisitorial elements in civil proceedings. A novelty of Soviet civil procedure as compared with the then European systems was the emergence of the constructive use of the institution of “abuse of rights” which determines the efficiency of civil proceedings. As a result, the Soviet civil procedure was a particular combination of the socialist rule of law and elements of classic European tradition, with a touch of the old pre-revolutionary Russian legal heritage and a small measure of new solutions compatible with the general direction of the development of the civil procedural law.
Keywords: Związek Radziecki; procedura cywilna; kodyfikacja; totalitaryzm; nowoczesność